ANIMASI E-LEARNING PEMBELAJARAN MATEMATIKA DAN FISIKA BAGI SISWA SEKOLAH MENENGAH PERTAMA KELAS 1 - Retnowati, Nurcahyani Dewi; Rahmawan, Mahmuda Ghazni (Sekolah Tinggi Teknologi Adisutjipto, 2016)
Learning through the use of animation E-Learning can be a learning tool to teach using electronic applications, media, Internet, Intranet or other computer network media. In addition to computers and Internet networks, which play a role in e-learning is the brainware that is creating content (text, images, video, animation) and user/users of e-learning (teachers and students). It should be noted in making animated e-learning is the content that should be included in accordance with the curriculum that is used by the school to be used for teaching and learning in schools. Making animated blueprint of learning by using characters then do modeling and animation. The subjects used in this study animation is Mathematics and Physics. Software used in the manufacture of learning applications that 3ds Max 2010, Adobe Premiere Pro CC, Adobe After Effects. The analysis tested the effectiveness of learning communication using questionnaire and calculation using a Likert scale that shows the percentage of 69.83%, the analysis proves that by using an animated e-learning teaching and learning activities in the classroom more effectively.